The Role of Law in Safeguarding Consumers in the Fast Beauty Industry: A Legal Analysis on Product Safety and Quality - Kathya Irsmi Sufa; Suparnyo (Dinasti Research, 2025)
The growth of the fast beauty industry in Indonesia presents serious challenges to consumer protection, particularly related to the circulation of illegal cosmetics, overclaims, and low understanding of product quality standards. This study aims to examine the implementation of consumer legal protection for fast beauty products in Kudus Regency, as well as to evaluate the extent to which ISO 9001:2015 quality standards are understood and implemented by business actors. This study uses an empirical legal approach with a qualitative design, and data collection techniques through in-depth interviews and documentation studies of regulations, business actors, regulators, medical personnel, and consumers. The research results indicate that consumer protection has not been optimally implemented due to weak oversight, limited resources, and low consumer literacy regarding product legality and safety. The implementation of ISO 9001:2015 is still limited to large-scale businesses, while small businesses do not yet understand the basic principles of quality management. These findings indicate the importance of integrating national legal regulations and international quality standards as a preventive strategy in the consumer protection system. In conclusion, consumer protection in the fast beauty industry requires a holistic legal approach based on regulation, quality, and education. This research contributes to broadening the conceptual framework of consumer protection law and provides a basis for policymakers to formulate more adaptive strategies to the dynamics of the modern cosmetics market. Future research is recommended to expand the geographic scope and use mixed methods to enhance the validity and generalizability of the findings.